Basket Weavers for the California Curio Trade : Elizabeth and Louise Hickox - Cohodas, Marvin (Book collections on Project MUSE., 1997)
Through its close examination of these superb practitioners of basketry, Basket Weavers for the California Curio Trade addresses many of today's most pressing questions in Native American art studies concerning individuality, patronage, and issues of authenticity. Graced with historical photographs and full-color plates, it reveals the challenges faced by early-twentieth-century Native weavers.